Przykłady zastosowania wnioskowania z bazy przypadków w informatycznych systemach wspomagających podejmowanie decyzji - Ratajczak, Tadeusz (Some Examples of Case-Based Reasoning Application in Informatics Decision Supporting Systems, 2005)
Case-based reasoning as a methodology of expert systems designing is shortly described at the beginning of the paper. Next, some informatics decision supporting systems to which application of case-based reasoning methodology resulted in the system efficiency increase are characterized. Finally, the basic principles for designing case-based systems are specified. Case-based reasoning as a methodology of expert systems designing is shortly described at the beginning of the paper. Next, some informatics decision supporting systems to which application of case-based reasoning methodology resulted in the system efficiency increase are characterized. Finally, the basic principles for designing case-based systems are specified.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 72-80